Between positivism and post-modernity? Critical reflections on Jock Young's The Exclusive Society - Yar, Majid (The British journal of criminology, 2004)
Jock Young's The Exclusive Society (1999) attempts to revitalize criminology's engagement with issues around social exclusion by drawing upon recent developments in the wider fields of social, cultural and political theory. In this article, we critically examine the relationship between this work and the traditions of realist and positivist criminology, and reflect upon the difficulties encountered by a criminology that draws upon accounts of modernity' and modernization' in order to explain the genesis of crime and recent shifts in crime control. We suggest that the tensions and difficulties thrown up by Young's account in fact epitomize challenges faced by critical criminologists more broadly, as they attempt to integrate established disciplinary concerns, concepts and methodologies with newer perspectives in social analysis, and to tackle the impact of processes of social change upon crime and criminalization